Investigação molecular da síndrome do x-frágil em portadores de transtornos do espectro autista na cidade de Manaus-Amazonas - Ferreira, Jorge Frank Braga (2016)
Fragile X Syndrome (FXS) is the main genetic condition associated to the development of Autism Spectrum Disorders (ASD) and hereditary Intellectual Deficiency (ID). Due to the variable expressivity of this syndrome and to its high prevalence among ASD patients, requiring screening tests for FXS is important for all individuals diagnosed with ASD and/or ID, because the presence of mutations in the FMR1 gene could lead to new options of treatment for the patient. In this study, the presence and the frequency of dynamic mutations in the FMR1 gene of 101 ASD patients has been verified by molecular analysis. There are few epidemiological data about the frequency of FXS in the Brazilian population and no study has already been performed in the State of Amazonas, so, this work provides a contribution to the prevalence of this syndrome in this Brazilian state. Keywords: FMR1. PCR. Dynamic mutation. CGG trinucleotide.